Evaluating South African environmental impact assessment (EIA) processes in the context of the Gautrain Project - Warburton, Catherine Lorna (My University, 2014)
This study analysed key elements of South African environmental impact assessment (EIA) statutory requirements through the lens of the Gautrain Project EIA. It identified alternative possible approaches to the EIA process for future infrastructure development projects. The EIA process components that are covered in the research are the responsibilities of the applicant, the Scoping Process, the Impact Assessment Process - including public participation and amendment processes, and the Environmental Management Plan (EMP) process. The requirements for these key components of the EIA process are identified and analysed, taking into account the EIA regulatory developments from 1997 to the current 2010 regulations. The EIA processes followed for the Gautrain Project are researched and analysed to identify process related flaws and deficiencies. It was found that the current application of the EIA requirements to large infrastructure development projects, such as the Gautrain Project, is unwieldy, costly and protracted and does not result in a comprehensive assessment of the impacts of these projects at the appropriate time – that is, when the project design has been finalised. The EIA process as currently legislated does not allow for an adaptable phased process approach. The Amendment Application and EMP process cannot cure this flaw, as was attempted in the Gautrain EIA process. A key finding is that in these infrastructure development projects, detailed data on potential impacts is only known at the stage of detailed design. At the stage of final design impact assessment should be conducted by the party that will ultimately carry the risk of and responsibility for the construction of the infrastructure. This could be achieved by allowing for an ‘in principle decision’ between scoping and the detailed EIA stage for the appointed Concessionaire, to proceed with detailed impact assessment, once it has further progressed its designs. The proposed approach in the recently tabled Infrastructure Development Bill is analysed and criticized. The incorporation of Strategic Environmental Assessment (SEA) in order to plan, streamline and focus the EIA process for infrastructure development projects is highly recommended.
Thesis (L.L.M. (Dissertation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Law, 2012.